MANFAAT HASIL BELAJAR LINSERI SEBAGAI KESIAPAN MEMBUKA USAHA LINSERI - Cannisa Ristiani Sholihah; As As Setiawati (Fesyen Perspektif, 2017)
This research investigates the benefits of learning lingerie as the readiness to open the business of lingerie. The purpose of this research is to get the data about the benefits of learning lingerie as the readiness to begin the business of lingerie which reviewed from the knowledge competence about the function of panty and bouste houder, the development of panty and bouste houder, the model of panty and bouste houder, the anatomy of panty and bouste houder, the material selections of panty and bouste houder, the techniques of measuring the body to make panty and bouste houder, the patterns of underwear and bouste houder, and the sewing techniques of underwear and bouste houder. The method used is descriptive quantitative method with the instruments of data collection in the form of questionnaire. The research sample used in this research is a saturation sampling where 33 students of fashion design of Indonesia University of Education batch 2011 involved. The result showed that more than half of the students stated the learning outcomes of lingerie in terms of knowledge competence of the functions of panty and bouste houder, briefs development and bouste houder,  the models of panty and bouste houder, the anatomy of panty and bouste houder, the materials selection of panty and bouste houder, the body measuring techniques to produce panty and bouste houder, the patterns of panty and bouste houder, and the sewing techniques of underwear and bouste houder. The conclusion of this research is more than half of the students feel the benefits of linseri business as the readiness to begin a business